Gallows Hill - Duncan, Lois 1934- (Random House, 1997)
When seventeen-year-old Sarah works in the fortune-telling booth at a school carnival, she finds that sometimes she can really see the future in the crystal ball, a talent that disturbs some of the other students and makes them suspect her of being a witch.